Perancangan Sistem Pengukuran Kinerja Perguruan Tinggi Melalui Metode Academic Scorecard - Dian J Permana (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Achievement of the quality of Performance of Higher Education (PT) can be seen from the achievement of the accredited rating of the study program and the accreditation rating of PT based on PermenRistek no. 32 Year 2016 on the Accreditation of Study Program and PT. The purpose of this research is to know the design of performance measurement system of PT the komperhenship. This study used the Academic Scorecard Method in combination with PermenRistek No. 44 Year 2015 on the National Standards of Higher Education to determine the content of each Cluster, while the stage of data processing and weighting of the design of PT performance measurement system using Analytic Network Process Method - ANP. Expert respondents numbered seven people who understand about performance measurement system of PT. The results of this study there are 3 stages in the design of performance measurement system of PT the komperhenship consisting of: 1). Input Stages contribute 68.72%, while this stage is divided into Cluster People consisting of three Higher Education Standards with a weight value of 52.54% and Cluster Resources consisting of six Standards of Higher Education with a weight value of 16.18%. 2). In-process stages that contribute 23.52%, while this stage is a Cluster Activities consisting of nine Standards of Higher Education. 3). Stages Output that contribute of 7.76%, while this stage is Cluster Output consisting of six Standards of Higher Education.